Copper Phthalocyanine MWCNTs Composites: Characterization and Evaluation for Sensor and Solar Cells interlayer - Kadem, Burak Yahya; Husein, Rand Kareem; Abbas, Zahraa Yassar (Iraqi Journal of Science, 2022)
Copper Phthalocyanine (CuPc) thin film with and without multi-walled carbon nanotubes (MWCNTs) is prepared using the solution based method and used in gas sensor and solar cell applications. The structural characteristics of the CuPc thin films showed a single peak around 7o with the preferred orientation for charge transportation. Using atomic force microscopy (AFM), morphological properties show a rough surface with some aggregates and ribbons. The optical absorption properties were determined using UV-Visible absorption spectroscopy; the optical band gap has varied after adding MWCNTs to CuPc. Electrical conductivity of CuPc:MWCNTs composite is higher than that of the pure CuPc. The CuPc thin film sensr have shown good response properties to ammonia gas. The solar cell performance of the P3HT:PCBM based solar cell was enhanced.